Mapas de distribución de algas marinas de la Península Ibérica e Islas Baleares. XXI. Sebdenia (Sebdeniaceae, Rhodophyta) - Gómez Garreta, Amelia; Ribera, Mª Antonia; Manghisi, Antonio (Botanica Complutensis, 2005)
The distribution maps along the Iberian Peninsula and the Balearic Islands of the genus Sebdenia (J. Agardh) Berthold, represented in this geographical area by two species: S. dichotoma Berthold and S. rodrigueziana (Feldmann) Parkinson, are given.
Keywords: Corology; Distribution; Maps; Marine algae; Sebdenia; Sebdeniaceae